1989
DOI: 10.1016/0016-7037(89)90211-1
|View full text |Cite
|
Sign up to set email alerts
|

An unusual mantle source region for nephelinites from the Oslo Rift, Norway

Abstract: Abstract-Wehave analyzed the trace-element and isotopic composition of a series of lavas and their constituent pyroxenes and calcite from near the town of Skien in the Permo-Carboniferous Oslo Rift. The series decreases in alkalinity upsection: the lowermost layaS are n~heli~t~, followed by basanites and finally alkali basalts. This sequence is accompanied by decreasing light ram earth element (LREE), Th, Nb and U concentrations. Nd isotopic change is strongly correlated with the petrologic and chemical evolut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0

Year Published

1991
1991
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 36 publications
(12 citation statements)
references
References 35 publications
1
11
0
Order By: Relevance
“…31, No. 1 melts (Anthony et al, 1989). The main mantle source for the basaltic magmatism was a prevalent depleted mantle.…”
Section: The Petrogenesis Of a High Volcanicity Riftmentioning
confidence: 99%
See 2 more Smart Citations
“…31, No. 1 melts (Anthony et al, 1989). The main mantle source for the basaltic magmatism was a prevalent depleted mantle.…”
Section: The Petrogenesis Of a High Volcanicity Riftmentioning
confidence: 99%
“…It may represent the composition of the base of the local lithospheric mantle, and the asthenosphere beneath, which partly melted in response to localized thinning of the lithosphere due to the extension. Anthony et al (1989) also suggested an alternative scenario involving a mantle plume, with depleted characteristics, actively up-welling beneath the lithosphere. The most primitive lavas appear to involve low degree partial melting of one or more sublithospheric mantle sources.…”
Section: The Petrogenesis Of a High Volcanicity Riftmentioning
confidence: 99%
See 1 more Smart Citation
“…A range of studies were made of comparable phenomena in other regions of the world: Red Sea Rift [ Hegner and Pallister , 1989], Ethiopian Rift [ Hart et al , 1989], Cameroon Line [ Halliday et al , 1988], Rhine Graben‐related volcanism [ Wörner et al , 1987; Harmon et al , 1987], the Oslo Rift [ Neumann et al , 1988; Anthony et al , 1989], the White Mountain plutons of the northeastern U.S. [ Foland et al , 1988] and the Deccan basalts [ Mahoney , 1988; Lightfoot and Hawkesworth , 1988]. Magma chamber phenomena, including assimilation, was studied at the Skaergaard Intrusion by Stewart and DePaolo [1990].…”
Section: Mantle Chemistry and Evolutionmentioning
confidence: 99%
“…[1989] presented a three component model that includes subducted crust and sediment, respectively. Baker [1987], Macdonald [1987] and Woolley and Jones [1987] described magmatism in the East African Rift, while Anthony et al . [1989] presented Sr and Nd isotopic data on nephelinites, basanites and alkali olivine basalts from the Oslo Rift.…”
Section: Intraplate and Rift‐related Volcanic And Plutonic Rocksmentioning
confidence: 99%